2005
DOI: 10.1037/0021-843x.114.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parental Depression With Psychiatric Course From Adolescence to Young Adulthood Among Formerly Depressed Individuals.

Abstract: We examined whether parental major depressive disorder (MDD) is associated with course of depression and other psychopathology among formerly depressed adolescents as they enter adulthood. The sample consisted of 244 individuals (age 24) in a longitudinal study who had experienced MDD by 19. Maternal MDD was associated with MDD recurrence, chronicity, and severity, anxiety disorders, and (among sons only) lower psychosocial functioning in offspring between 19-24. Paternal MDD was associated with lower function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 100 publications
3
33
0
Order By: Relevance
“…The results are also consistent with longitudinal studies of offspring of depressed parents that have shown associations of parental depression with recurrent youth depression (e.g., Lieb et al 2002;Rohde et al 2005;Weissman et al 1997). Those studies did not test for mediational effects, however, and the current study is the first to suggest that maternal depression did not have strong direct effects on depression occurring later in adolescence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results are also consistent with longitudinal studies of offspring of depressed parents that have shown associations of parental depression with recurrent youth depression (e.g., Lieb et al 2002;Rohde et al 2005;Weissman et al 1997). Those studies did not test for mediational effects, however, and the current study is the first to suggest that maternal depression did not have strong direct effects on depression occurring later in adolescence.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, Lewinsohn et al (2000) found that youth with prior depression were more likely to have recurrence by early adulthood if they had multiple previous episodes, family members with major depressive disorder, and for females, family conflict. Rohde et al (2005) in the same sample found that maternal major depression was predictive of youth recurrence of depression among those with previous depression. Essau (2004), in a large cross sectional study of adolescents, also found an association between youth reports of recurrent depression and maternal history of depression.…”
mentioning
confidence: 86%
“…Interviewer performance was carefully monitored to maintain reliability. We previously reported that inter-rater reliabilities ( n = 263 at T1; 162 at T2; 190 at T3; and 124 at T4) indicated good to excellent agreement for both MDD ( k = .81-.86) and nonmood disorders ( k = .76-.89) (Rohde, Lewinsohn, Klein, & Seeley, 2005; Seeley, Kosty, Farmer, & Lewinsohn, 2011). …”
Section: Methodsmentioning
confidence: 95%
“…Children of depressed parents often show diminished affect regulation and cognitive and language functioning when their mothers are depressed (e.g., Carter et al, 2001;Cicchetti et al, 1998;Rohde et al, 2005). They are at risk for developing depressive disorders themselves (Sim and England, 2009) and other internalizing and externalizing disorders (Lyons-Ruth et al, 1997).…”
Section: Introductionmentioning
confidence: 97%